A Genome-Wide Detection of Copy Number Variations Using SNP Genotyping Arrays in Braque Français Type Pyrénées Dogs - Rosalia Di Gerlando; Salvatore Mastrangelo; Maria Teresa Sardina; Marco Ragatzu; Andrea Spaterna; Baldassare Portolano; Filippo Biscarini; Roberta Ciampolini (Animals, 2019)
Copy number variants (CNVs) are an important source of genetic variation complementary to single nucleotide polymorphisms (SNPs). Only few studies have been conducted in dogs on CNVs derived from high-density SNP array data, and many canine breeds still remain uncharacterized, e.g., the Braque Français, type Pyrénées breed (BRA). Therefore, in an effort to more comprehensively investigate the canine genome for CNVs, we used a high-density SNP array (170 K) to discover CNVs in BRA. The CNV regions (CNVRs) were identified through the merging of two different CNVRs datasets, obtained separately from SNP data using the PennCNV and SVS software. A total of 45 stringent CNVRs, ranging from 3.5 kb to 458,716 kb in length were detected in 26 dog samples. Results overlapped moderately in comparison with previous studies on CNVs in dogs, leading to the identification of 16 novel CNVRs. A total of 159 genes were annotated in the CNVRs detected with stringent quality criteria in particular high classification stringency and false discovery rate correction. The gene ontology enrichment analysis provided information on biological processes and cellular components related to muscle structure development and muscle cell differentiation. Considering that BRA is a breed used for speed in hunting and retrieval, for the ability to find feathered game, and for pointing, we can hypothesize that selection for such hunting behavior could have driven, at least in part, the presence of these genes into the CNVRs.